Dini grupların birey ve toplum üzerindeki etkileri: İlahiyat fakültesi öğrencileri üzerine bir araştırma - Suat CEBECİ; Kübra CEVHERLİ; Feyza DOĞRUYOL; Büşra ÇAKMAKTAŞ; Zehra ÖZLİ (Türkiye Din Eğitimi Araştırmaları Dergisi)
Religious groups supported by sensitivities in the field of religion and spirituality are a reality of the social life. It is a fact that these structures, which manifest themselves in the form of sects and communities, perform some functions that have important consequences for individuals and societies. Providing religious groups for members socialization opportunity, eliminating loneliness and gaining some virtues are the factors that provide interest and commitment to the group. Besides, the most significant negative effects of religious groups are the fact that it does not allow free thought and self-criticism, urges on exclusionist attitudes towards people outside the group, and makes the members easily motivated with absolute obedience to group leaders. The interpretations and evaluations made by the students at theology faculties about these effects and functions are important because they are educated with the mission of giving direction to the society on religious issues. For this reason, the opinions of these students from different regions have been taken by applying them a questionnaire. According to the data obtained from the study, it is concluded that almost half of the students have not agreed with the belief that religious groups are harmful to the society and that more than half of them have believed that religious groups provided useful services to the people and the society. In addition, almost half of the students (44%) think that religious groups blinded the skills of free thought and criticism of their members. It has been found that 60% of those who stated that they belonged to a religious group are in this opinion.